PERTIMBANGAN UU ITE DALAM TINDAK PIDANA PENYEBARAN GAMBAR PORNOGRAFI (PUTUSAN NOMOR 563/PID.SUS-/2020/PN.BGL): Consideration Of The EIT Law in The Crimina Act of Distributing Pornographic Images (Decision Number 563 / Pid. Sus-/2020/Pn. Bgl) - Encik Inne Alifia Audina; Ermania Widjajanti (AMICUS CURIAE, 2024)
The perpetrator Julianda deliberately and knowingly posted nude images of the victim Murni Januasari to socia media accounts in the form of Facebook and Instagram belonging to the victim which he did without prior permission and had deviated from the rules in Article 27 paragraph (1) jo Article 45 paragraph (1) of the EIT Law. The Subject Matter raised by the Author is 1.) How did the judge consider in the case of decision No. 563/PID. Sus/2020/PN.Bgl reviewed from Article 27 Paragraph (1) of the EIT Law Jo Article 45 Paragraph (1) EIT Law on the dissemination of immora content on socia media? 2.) Is the conviction of the perpetrator who has been decided by the judge in decision 563/Pid. Sus/2020/PN.Bgl in accordance with the purpose of punishment? This research uses a normative type that is descriptive anaytica, data collection using secondary data obtained through literature studies and data processed quaitatively using deductive logic conclusions. As for the conclusions of this study 1.) The defendant has fulfilled the elements contained in Article 27 paragraph (1) of the EIT Law Jo Article 45 paragraph (1) of the EIT Law. The first element is the element of everyone, the second element is the existence of elements intentionaly and without rights, the third element is the element of distributing and / or transmitting and / or making accessible electronic information and / or electronic documents that have content that violates decency. 2.) The crimina conviction of the accused is in accordance with the magnitude of the mistake committed by the defendant.